TiO2 nanorods and Pt nanoparticles under a UV-LED for an NO2 gas sensor at room temperature - Noh, Jinhong (2021)
Because the oxides of nitrogen (NOx) cause detrimental effects on not only the environment but humans, developing a high-performance NO2 gas sensor is a crucial issue for real-time monitoring. To this end, metal oxide semiconductors have been employed for sensor materials. Because in general, semiconductor-type gas sensors require a high working temperature, photoactiva-tion has emerged as an alternative method for realizing the sensor working at room temperature. In this regard, titanium dioxide (TiO2) is a promising material for its photocatalytic ability with ultraviolet (UV) photonic energy. However, TiO2-based sensors inevitably encounter a problem of re-combination of photogenerated electron-hole pairs, which occurs in a short time. To address this challenge, in this study, TiO2 nanorods (NRs) and Pt nanoparticles (NPs) under a UV-LED were used as an NO2 gas sensor to utilize the Schottky barrier formed at the TiO2-Pt junction, thereby capturing the photoactivated electrons by Pt NPs. The separation between the electron-hole pairs might be further enhanced by plasmonic effects. In addition, it is reported that annealing TiO2 NRs can achieve noteworthy improvements in sensing performance. Elucidation of the performance enhancement is suggested with the investigation of the X-ray diffraction patterns, which implies that the crystallinity was improved by the annealing process.